Nasal Tip Projection: Nuances in Understanding, Assessment, and Modification - Robinson, Simon; Thornton, Mona (Facial Plastic Surgery, 2012)
Nasal tip projection refers to the anteroposterior extent to which the nasal tip is separated from the facial surface at the level of the alar-facial groove. Although its relevance in rhinoplasty is obvious, it is important to understand that changes to the projection of the nasal tip affect nasal tip rotation, dorsal height, and nasofacial aesthetic harmony. The following article discusses the subjective and objective assessment of nasal tip projection, the relevant anatomy, and tools to plan ways of modifying aspects of tip projection. Several different techniques will then be described in detail, along with relevant clinical illustrations.
Keywords: projection; nasal tip; rhinoplasty